2021
DOI: 10.1002/ajoc.202100025
|View full text |Cite
|
Sign up to set email alerts
|

Recent Dearomatization Strategies of Benzofurans and Benzothiophenes

Abstract: This review article discusses about the recent developments in the area of the strategies for the dearomatization of benzofurans and benzothiophenes (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020). The readers can understand the current state of art of this intriguingly important area in organic synthesis for the generation of diversely functionalized molecules, polycyclic systems from highly abundant benzofurans and benzothiophenes. We hope that the current review article would help the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 90 publications
0
20
0
Order By: Relevance
“…7 Along these lines, benzofuran dearomatization is a straightforward route to 2,3-dihydrobenzofurans. 8 Known dearomatization strategies involve cycloaddition, 9 14 direct hydrogenation, 15 , 16 cyclopropanation, 17 radical cyclization, 18 20 and radical addition 21 among other reactions. 22 27 Halofunctionalizations have been used for benzofuran dearomatization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Along these lines, benzofuran dearomatization is a straightforward route to 2,3-dihydrobenzofurans. 8 Known dearomatization strategies involve cycloaddition, 9 14 direct hydrogenation, 15 , 16 cyclopropanation, 17 radical cyclization, 18 20 and radical addition 21 among other reactions. 22 27 Halofunctionalizations have been used for benzofuran dearomatization.…”
mentioning
confidence: 99%
“…2,3-Dihydrobenzofurans are core motifs that appear in biologically active compounds (Scheme a). , For example, DNA-PK inhibitors, CB 2 receptor agonists, and furaquinocin A contain a functionalized 2,3-dihydrobenzofuran scaffold. Therefore, it is important to develop methods to access such compounds . Along these lines, benzofuran dearomatization is a straightforward route to 2,3-dihydrobenzofurans . Known dearomatization strategies involve cycloaddition, direct hydrogenation, , cyclopropanation, radical cyclization, and radical addition among other reactions. Halofunctionalizations have been used for benzofuran dearomatization. However, a multistep operation for prior installation of substituents bearing nucleophilic moieties is generally required in these halofunctionalizations.…”
mentioning
confidence: 99%
“…In recent years, electron-deficient nitroheteroarenes, including nitroindoles, nitrobenzofurans, and nitrobenzothiophenes, have shown powerful applications in various dearomative cycloadditions for the construction of structurally diverse polyheterocyclic compounds. 8 Among these, most of the reported cycloaddition reactions are confined to the 6π-electrons-type cycloaddition (Scheme 1a). 9 In contrast, the higher-order cycloaddition reaction (> 6π-electrons) with respect to electron-deficient nitroheteroarenes has remained unexplored (Scheme 1a).…”
mentioning
confidence: 99%
“…Among various aromatics and heteroaromatics, , the dearomative spirocyclization of thiophenes is underdeveloped, probably due to their relatively high resonance stabilization energy (∼22 kcal mol –1 ). For instance, Wright and co-workers have shown that the electrochemical dearomative spirocyclization of the C2-tethered furan readily proceeded with C2-spirocyclization (Scheme A) . When it is transferred to the analogous thiophene derivative, however, a nonselective C2 and C3 Friedel–Crafts type alkylation took place, followed by downstream chemical and electrochemical transformations, to generate both C3-annulation and C2-spirocyclization products.…”
mentioning
confidence: 99%